Regionalny system innowacji jako przestrzeń dla tworzenia pozycji konkurencyjnej gospodarki - Mamica, Łukasz (Regional Innovation System as a Space for Creating Economic Competitiveness, 2009)
Regional Innovation Systems are characterized by different factors and among them the most important role play human capital. Firms, institutions and R&D supplier interact in many directions. Industrial clusters functioning within regions are examples of the use of rare resources which are accumulated there. The development of mathematics and theoretical engineering under the conditions of central driven economy before 1989 in Małopolska, which created later success of information technologies and human capital, was stimulated by the lack of physical equipment and laboratories. Unwillingness of IT specialists to change their places of living has an influence on comparative advantage of Małopolska as an attractive destination of foreign investments in this sector. The fact that in Cracow exist branches of such global companies as IBM, Motorola, Google, Delphi confirms the attractiveness of this region. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 724-732